O godności w polityce - Suchocka, Hanna (Horyzonty Wychowania, 2017)
Looking for the link between dignity and politics, the authorquotes popular encyclopaedic definitions, which suggest that anobvious aim of every political action is gaining or keeping power.And since the aim of political authority should be serving thegeneral good, decisions made by politicians should be based onvalues identifying the rights of individual citizens. The best protectionfor these rights is respecting the natural law, however inmany countries binding regulations do not refer to this basic normdirectly. Therefore, dignity is not always treated as a fundamentalcharacteristic of every human being, though usually politicsassumes concern for citizens’ dignity, their decent life etc.In Polish political experiences of the second half of the 20thcentury the principle of solidarity had an important position, asthe opposite of the principle of class hatred (class struggle) thecommunists subscribed to. Solidarity, chosen as the motto bya huge social movement, was a protest against indecent livingconditions, and at the same time striving after practising decentpolitics, i.e. honest and based on the truth.